Accessing health information during the COVID-19 pandemic: the experience of NHS maternity service users - Rushvini Ambihaipahan; Georgia Chisnall; Cecilia Vindrola-Padros; Lucy Irvine (BMC, 2023)
Abstract Background The COVID-19 pandemic caused various disruptions to NHS maternity services in England. Changes were made to antenatal and postnatal care and the way that information was shared with maternity service users during these times. Fewer face-to-face appointments, increased virtual appointments and changes in guidance about the suitability of the COVID-19 vaccine without appropriate information sharing and evidence caused concern. Methods This study took a blended inductive-deductive approach to secondary data analysis using a population subset of 16 from a wider study that sought to understand the impact of COVID-19 on maternity services in England. Participants of this study were aged 28-44 and gave birth using NHS maternity services in England. The data were collected and coded using Rapid Analysis Procedure sheets, which generated key themes, which are used here to structure the results. Results Four main themes were generated from the analysis: 1) service restrictions to antenatal and postnatal appointments 2) access to information and changes to antenatal and postnatal care 3) inconsistencies in the implementation of government and NHS policy and 4) limited information about COVID-19 vaccine provided by NHS trusts and hesitancy in vaccine acceptance. Conclusion Participants experienced poor communication that affected their understanding of maternity service changes and there was limited general and maternal health information provided. Vaccine information was also inadequate, and participants expressed a desire for clearer guidance. The UK Government, Royal College of Obstetricians and Gynaecologists, and NHS must collaborate with maternity service users to ensure that there are evidence-based guidelines and policies that can be understood and standardised across all NHS maternity trusts.